Polymer solid electrolyte
A solid polymer electrolyte with a urethane resin and specific components addresses the elasticity and compatibility issues of gel electrolytes, offering improved safety and performance through enhanced elasticity, stretchability, and conductivity.
Patent Information
- Application Number
- JP2023092628
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
AI Technical Summary
Gel electrolytes using polyvinylidene fluoride-hexafluoropropylene copolymers lack sufficient elasticity and compatibility with carbonate-based electrolytes, leading to poor electrolyte retention and volatility, which affects battery safety and performance.
A solid polymer electrolyte composed of a urethane resin containing polyalkylene oxide, a polyol with three or more hydroxyl groups, and an isocyanate, with specific molecular weight ranges and SP value differences, achieving high elasticity, stretchability, electrolyte retention, and flame retardancy.
The solution provides a solid polymer electrolyte with improved elasticity, stretchability, electrolyte retention, and high ionic conductivity, enhancing battery safety and performance.
Smart Images

Figure 2024174673000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer solid electrolyte. [Background technology]
[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to protect the environment. In the automobile industry, there is hope that the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs) will help reduce carbon dioxide emissions, and efforts are being made to develop secondary batteries for driving motors, which hold the key to putting these vehicles to practical use. As a secondary battery, lithium-ion batteries, which can achieve high energy density and high power density, have been attracting attention.
[0003] Among these, lithium-ion secondary batteries using polymer solid electrolytes are being considered as batteries that are unlikely to volatilize organic solvents and do not suffer from the problem of battery expansion caused by gas generation inside the battery due to the progress of the decomposition reaction of the organic solvent, a side reaction during charging and discharging. For example, Patent Document 1 discloses a gel electrolyte that combines a polyvinylidene fluoride-hexafluoropropylene copolymer, which is a material that has excellent chemical and electrochemical stability inside a battery, with a carbonate-based electrolyte solution. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-141467 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, gel electrolytes using polyvinylidene fluoride-hexafluoropropylene copolymers have problems in that the electrolyte does not have sufficient elasticity and stretchability, and cannot keep up with the expansion and contraction of the electrodes that accompany repeated charging and discharging, resulting in a significant decrease in battery capacity over long-term use.In addition, the compatibility between polyvinylidene fluoride-hexafluoropropylene copolymers and carbonate-based electrolytes is poor, resulting in poor electrolyte retention, and the volatility of carbonate-based electrolytes means there is room for improvement in terms of battery safety.
[0006] The present invention has been made in view of the above circumstances, and has an object to provide a polymer solid electrolyte that simultaneously achieves high elasticity, stretchability, electrolyte retention, flame retardancy (low flash point), and high ionic conductivity. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors arrived at the present invention. The present invention relates to a polymer solid electrolyte comprising a urethane resin and an electrolytic solution, the urethane resin being a reaction product of a composition comprising a polyalkylene oxide (A-1), a polyol (A-2) having three or more hydroxyl groups, and an isocyanate (B), the urethane resin having a crosslink density of 5 to 21 mmol / kg, the electrolytic solution comprising an electrolyte and an electrolytic solution solvent (C), and the absolute value of the difference between the SP value of the polyalkylene oxide (A-1) and the SP value of the electrolytic solution solvent (C) is 4.0 or less. Effect of the Invention
[0008] According to the present invention, it is possible to provide a polymer solid electrolyte that simultaneously achieves high elasticity, stretchability, electrolyte retention, flame retardancy (low flash point), and high ionic conductivity. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 shows the results of evaluation of the elasticity of the polymer solid electrolyte (measurement of hysteresis loss). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The polymer solid electrolyte of the present invention comprises a urethane resin and an electrolytic solution, and the urethane resin is a reaction product of a composition comprising a polyalkylene oxide (A-1), a polyol (A-2) having three or more hydroxyl groups, and an isocyanate (B).
[0011] The polyalkylene oxide (A-1) in the present invention is obtained by an addition reaction of an alkylene oxide having 2 to 4 carbon atoms, and is represented by the general formula H(OA)nOH, where A is a linear or branched alkyl group having 2 to 4 carbon atoms, and has a number average molecular weight (Mn) of preferably 200 to 20,000, more preferably 600 to 10,000, and even more preferably 600 to 8,000. When the number average molecular weight of the polyalkylene oxide (A-1) is within the above numerical range, the viscoelasticity and stretchability of the resulting polymer solid electrolyte are improved.
[0012] The polyalkylene oxide (A-1) is preferably polyethylene glycol, polypropylene glycol, or a block thereof. The polyethylene glycol may be of the general formula H(OCH2-CH2)nOH, where n is preferably 3 to 450, more preferably 4 to 100, from the viewpoint of the viscoelasticity and elasticity of the resulting polymer solid electrolyte. For example, "PEG-200, PEG-1000, PEG-1540, PEG-2000, PG20000 manufactured by Sanyo Chemical Industries, Ltd." may be used, and these are commercially available. From the viewpoint of the viscoelasticity and elasticity of the resulting polymer solid electrolyte, polyethylene glycol having a number average molecular weight of 200 to 1,000 is preferred, and polyethylene glycol having a number average molecular weight of 200 to 500 is more preferred.
[0013] The polypropylene glycol may be polypropylene glycol of the general formula H(OCH2-CH(CH3))nOH, where n is preferably 3 to 100, more preferably 5 to 100, from the viewpoint of the viscoelasticity and elasticity of the resulting polymer solid electrolyte. For example, "PPG-200, PPG-400, PPG-600, PPG-4000 manufactured by Sanyo Chemical Industries, Ltd." may be used, and these are commercially available. From the viewpoint of the viscoelasticity and elasticity of the resulting polymer solid electrolyte, polypropylene glycol having a number average molecular weight of 600 to 10,000 is preferred, and more preferably a number average molecular weight of 600 to 5,000 is preferred.
[0014] As the block copolymer of polyethylene glycol and polypropylene glycol, for example, "PE-68 (manufactured by Sanyo Chemical Industries, Ltd.)" can be used, and it is commercially available.
[0015] The number average molecular weight of the polyalkylene oxide (A-1) is measured by gel permeation chromatography (hereinafter sometimes abbreviated as GPC) under the following conditions.
[0016] <Gel permeation chromatography conditions> Device body: HLC-8420 (Tosoh Corporation) Column: Tosoh Corporation TSKgel Super H4000, H3000, H2000 Detector: RI (Refractive Index) Eluent:THF Eluent flow rate: 0.6ml / min Column temperature: 40℃ Sample concentration: 0.25% by weight Injection volume: 10μl Standard material: TSK STANDARD POLYSTYRENE manufactured by Tosoh Corporation Data processing software: EcoSEC Elite-WS analysis (Tosoh Corporation)
[0017] In the present invention, the polyalkylene oxide (A-1) preferably contains two or more kinds of polyalkylene oxides, for example, a combination of polyethylene glycol and polypropylene glycol, from the viewpoint of the viscoelasticity and elasticity of the resulting polymer solid electrolyte.
[0018] In the present invention, examples of the polyol (A-2) having three or more hydroxyl groups include alkane polyols and their intramolecular or intermolecular dehydration products, such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, polyglycerin, and dipentaerythritol.
[0019] Examples of the isocyanate (B) in the present invention include aliphatic isocyanates (b1) having 2 to 18 carbon atoms (excluding carbon atoms in NCO groups, the same applies below), araliphatic isocyanates (b2) having 8 to 15 carbon atoms, aromatic isocyanates (b3) having 6 to 20 carbon atoms, and isocyanate-modified products (b4) of these having an isocyanurate group, a uretoimine group, an allophanate group, a biuret group, a carbodiimide group and / or a uretdione group. One type of isocyanate (B) may be used alone, or two or more types may be used in combination.
[0020] Examples of the aliphatic isocyanate (b1) having 2 to 18 carbon atoms include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), heptamethylene diisocyanate, octamethylene diisocyanate, decamethylene diisocyanate, dodecamethylene diisocyanate, 2,2,4- or 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2,6-diisocyanatomethyl capro ... triethyl caproate, bis(2-isocyanatoethyl) fumarate, bis(2-isocyanatoethyl) carbonate, isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, and 2,5- or 2,6-norbornane diisocyanate.
[0021] Examples of the aralkylisocyanate (b2) having 8 to 15 carbon atoms include m- or p-xylylene diisocyanate (XDI), diethylbenzene diisocyanate, and α,α,α',α'-tetramethylxylylene diisocyanate (TMXDI).
[0022] Examples of the aromatic isocyanate (b3) having 6 to 20 carbon atoms include 1,3- or 1,4-phenylene diisocyanate, 2,4- or 2,6-tolylene diisocyanate (TDI), 4,4'- or 2,4'-diphenylmethane diisocyanate (MDI), m- or p-isocyanatophenylsulfonyl isocyanate, 4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatodiphenylmethane, and 1,5-naphthylene diisocyanate.
[0023] Examples of the isocyanate modified product (b4) having an isocyanurate group, a uretoimine group, an allophanate group, a biuret group, a carbodiimide group, and / or a uretdione group include a modified product of MDI having a uretoimine group, a modified product of HDI having a biuret group, and a modified product of HDI having an isocyanurate group.
[0024] As the isocyanate (B), from the viewpoint of elasticity and stretchability of the resulting polymer solid electrolyte, MDI is preferred, and polymeric MDI is more preferred. Polymeric MDI is a mixture of monomeric MDI with various isomer contents and polynuclear MDI with several structures.
[0025] The crosslink density of the urethane resin in the present invention is 5 to 21 mmol / kg. If the crosslink density of the urethane resin is less than 5 mmol / kg, the viscoelasticity and liquid retention of the polymer solid electrolyte deteriorates, whereas if the crosslink density of the urethane resin is more than 21 mmol / kg, the elasticity and liquid retention of the polymer solid electrolyte deteriorates. The crosslink density of the urethane resin can be adjusted by the amount of the polyol (A-2) having three or more hydroxyl groups added.
[0026] In the present application, the crosslink density is calculated by the following formula. V = Mp / Wp (1) V: Crosslink density (mmol / kg) Mp: the number of moles of (A-2) Wp:Wg - Wl Wg: Weight of polymer solid electrolyte (kg) Wl: Weight of electrolyte contained in polymer solid electrolyte (electrolyte + electrolyte solvent)
[0027] The electrolytic solution in the present invention comprises an electrolyte and an electrolytic solution solvent (C). The electrolyte can be any known lithium salt used in lithium ion batteries, and examples of such electrolytes include inorganic acid lithium salt electrolytes such as LiCF3SO3, LiPF6, LiBF4, LiSbF6, LiAsF6, and LiClO4; sulfonylimide electrolytes such as LiFSi, LiN(FSO2)2, LiN(CF3SO2)2, LiN(C2F5SO2)2, and LiC2F3NO4S2 (LiTFSI); and sulfonylmethide electrolytes having a fluorine atom such as LiC(CF3SO2)3. From the viewpoint of thermal stability and hydrolysis resistance, the electrolyte is preferably a sulfonylimide electrolyte.
[0028] The electrolyte solvent (C) preferably has a flash point of 100° C. or higher. When the electrolyte solvent (C) has a flash point of 100° C. or higher, the safety (flame retardancy) of the polymer solid electrolyte is improved. As the electrolyte solvent (C), a mixture of multiple solvents may be used. As long as the electrolyte solvent after mixing has a flash point of 100°C, a solvent having a flash point of less than 100°C may be included. Examples of the electrolyte solvent include dimethyl carbonate, ethylene carbonate (EC), ethyl methyl carbonate, diethyl carbonate, ethyl propyl carbonate (EPC), dipropyl carbonate (DPC), dipropylene glycol dimethyl ether, tripropylene glycol dimethyl ether, tetrapropylene glycol dimethyl ether, diglyme, triglyme, tetraglyme, and sulfolane.
[0029] In this specification, the flash points of the electrolyte solvent and the electrolyte are temperatures measured by the tag seal method specified in JIS K 2265-1-2007.
[0030] In the present invention, the absolute value of the difference between the SP value of the polyalkylene oxide (A-1) and the SP value of the electrolyte solvent (C) is 4.0 or less. If the absolute value of the difference in the SP values exceeds 4.0, the electrolyte retention and safety (flame retardancy) of the polymer solid electrolyte deteriorate. The (A-1) and the (C) may each be a mixture of two or more kinds. In that case, the SP value is a weighted average of values calculated by the following method.
[0031] In this application, the SP value (solubility parameter) [unit: (cal / cm 3 ) 1 / 2 ] is a value calculated by the method described in formula (28) on page 153 of the Fedors method (Polymer Engineering and Science, February, 1974, Vol. 14, No. 2, pp. 147-154) using the values (heat of vaporization and molar volume at 25°C of atoms or functional groups) described on page 152 (Table. 5) of the Fedors method. Specifically, it can be calculated by applying the values of Δei and Δvi described in Table 1 below, which are parameters of the Fedors method, to the following formula (2) using the values corresponding to the types of atoms and atomic groups in the molecular structure. SP value = (ΣΔei / ΣΔvi) 1 / 2 (2) In the above formula, ΣΔei (unit: cal / mol) is the cohesive energy density (unit: cal / mol), and ΣΔvi is the molar volume (unit: cm3 / mol).
[0032] [Table 1]
[0033] From the viewpoint of compatibility with the electrolyte, the polyalkylene oxide (A-1) preferably has an SP value of 8 to 11. From the viewpoints of ion conductivity and compatibility with the matrix polymer, the electrolyte solvent (C) preferably has an SP value of 8 to 14.
[0034] In addition to the above-mentioned components, the polymer solid electrolyte of the present invention may contain additives used in ordinary polymer compounds within the scope of the present invention. Examples of the additives include stabilizers such as antioxidants, heat stabilizers, and light resistance stabilizers; ultraviolet absorbers; fillers such as inorganic fillers and organic fillers; lubricants; release agents; plasticizers; and antistatic agents.
[0035] The polymer solid electrolyte of the present invention can be produced by mixing all the components constituting the polymer solid electrolyte, and then heating the mixture to 50° C. to 100° C. to cure it. EXAMPLES
[0036] The present invention will now be described in detail with reference to examples. However, the present invention is not limited to these examples as long as it does not depart from the gist of the present invention.
[0037] <Preparation of electrolyte> A stirrer and 12.7 parts by weight of tripropylene glycol dimethyl ether (manufactured by Tokyo Chemical Industry Co., Ltd.) were added to a reaction vessel that had been dried for one day in an environment with a temperature of 19°C and a dew point of -60°C dp, and the mixture was stirred with a magnetic stirrer. 7.55 parts by weight of lithium (bisfluorosulfonyl)imide (manufactured by Kishida Chemical Co., Ltd.) and 8.2 parts by weight of ethylene carbonate (manufactured by Tokyo Chemical Industry Co., Ltd.) were added thereto, dissolved, and homogenized to prepare an electrolyte solution.
[0038] Example 1 To 69.9 parts by weight of the prepared electrolyte, 0.4 parts by weight of a trifunctional propylene oxide adduct having a number average molecular weight of 250 (Sanyo Chemical Industries, Ltd., Sannix GP-250), 1.2 parts by weight of a bifunctional polypropylene oxide having a number average molecular weight of 600 (Sanyo Chemical Industries, Ltd., Sannix PPG-600), and 25.3 parts by weight of a bifunctional polypropylene oxide having a number average molecular weight of 4000 (Sanyo Chemical Industries, Ltd., Sannix PPG-4000) were added. Then, 0.2 parts by weight of a bismuth-based metal catalyst (Nitto Chemical Industries, Ltd., Neostan U-600) was added and stirred for 10 minutes to obtain a transparent and uniform polyalcohol liquid. 3.0 parts by weight of polymeric MDI (Millionate MR-200, manufactured by Tosoh Corporation) was added to the prepared polyalcohol solution and stirred for 5 minutes to obtain a pale yellow liquid. The obtained pale yellow liquid was degassed under reduced pressure at 19°C for 30 minutes in a bell jar to prepare a polymer electrolyte precursor. The polymer electrolyte precursor was gently poured into a 5cm x 10cm square PP tray, and the precursor was spread over the entire bottom of the tray. The temperature was then adjusted to 80°C for 3 hours in a thermostatic chamber with a leveled surface. After adjustment, the polymer electrolyte was peeled off from the PP tray to obtain a pale yellow transparent polymer solid electrolyte. The thickness of the polymer solid electrolyte measured with a thickness gauge was 500μm.
[0039] (Examples 2 to 12, Comparative Examples 1 to 4) As shown in Tables 2 and 3, polymer solid electrolytes according to Examples 2 to 12 and Comparative Examples 1 to 4 were prepared in the same manner as in Example 1, except that the various constituent types and weight ratios were changed.
[0040] [Table 2]
[0041] [Table 3]
[0042] Details of the abbreviations listed in Tables 1 and 2 are as follows: PPG-4000: Polypropylene glycol [manufactured by Sanyo Chemical Industries, Ltd.] PPG-600: Polypropylene glycol [manufactured by Sanyo Chemical Industries, Ltd.] PEG-200: Polyethylene glycol [Sanyo Chemical Industries, Ltd.] PEG-20000: Polyethylene glycol [manufactured by Sanyo Chemical Industries, Ltd.] PE-68: "Newpol PE-68" [manufactured by Sanyo Chemical Industries, Ltd.] GP-250: "Sannix GP-250", trifunctional propylene oxide adduct [manufactured by Sanyo Chemical Industries, Ltd.] TMP: Trimethylolpropane [Tokyo Chemical Industry Co., Ltd.] PG3: Tripropylene glycol dimethyl ether [FUJIFILM Wako Pure Chemical Industries, Ltd.] G4: Tetraethylene glycol dimethyl ether (tetraglyme) [Kishida Chemical Co., Ltd.] SL: Sulfolane [FUJIFILM Wako Pure Chemical Industries, Ltd.] DEC: Diethyl carbonate [Tokyo Chemical Industry Co., Ltd.] EC: Ethylene carbonate [Tokyo Chemical Industry Co., Ltd.]
[0043] <Elasticity evaluation> The obtained polymer solid electrolyte was punched into a circle with a diameter of 8 mm to prepare a sample for evaluating the elastic modulus. The sample was sandwiched between parallel plates with a diameter of 8 mm of a rheometer ("MCR-802" manufactured by Anton Paar), and the gap between the plates was adjusted so that the normal force was 1.0 N when the temperature was controlled at 25°C. The storage elastic modulus (G') was measured at a shear of 1 Hz under a condition of a rotational strain of 2%. The results are shown in Tables 4 and 5.
[0044] <Ionic conductivity evaluation> The obtained solid polymer electrolyte was punched into a circle with a diameter of 18 mm to prepare a sample for evaluating ionic conductivity. The sample was sandwiched between two pieces of Li metal (manufactured by Honjo Metals Co., Ltd., Li-Foil: thickness 0.5 mm) punched into a circle with a diameter of 16 mm, and a stainless steel metal electrode was placed on the outside. Impedance measurements were performed in a constant temperature bath controlled at 25°C using an electrochemical measurement device "VSP-300" made by BioLogic Co., Ltd. in the frequency range of 7 MHz to 1 Hz. The semicircle on the high frequency side in the obtained Nyquist plot was taken as the bulk resistance R of the sample, and the ionic conductivity δ was calculated from the thickness d of the sample and the opposing area A with the Li metal using the following formula. The results are shown in Tables 4 and 5. δ = d / (R × A)
[0045] <Measurement of electrolyte retention rate> The obtained solid polymer electrolyte was cut into 20 mm x 20 mm squares to prepare samples for evaluating electrolyte retention. Three PP separators ("Celgard #3501") cut into 30 mm x 30 mm squares were placed on both sides of the sample, and the sample was sandwiched between 10 mm thick, 60 mm x 100 mm square stainless steel plates. A weight was placed on the upper stainless steel plate so that the load on the sample was 4 kg, and the temperature was controlled at 25 ° C for 48 hours. After the temperature control was completed, six separators were taken out, and the electrolyte retention was calculated from the weight before evaluation W0, the weight after evaluation W1, and the initial weight of the sample S0 using the following formula. The results are shown in Tables 4 and 5. Electrolyte retention rate=(1-((W1-W0) / S0))×100(%)
[0046] <Hysteresis loss measurement: Elasticity evaluation> The obtained polymer electrolyte was punched out into a No. 2 dumbbell shape to prepare a sample for evaluating hysteresis loss. Hysteresis loss was measured using the control mode of an autograph ("AG-X" manufactured by Shimadzu Corporation) by pulling from a mark of 20 mm to a stroke of 10 mm at a pulling speed of 20 mm / min, and then returning the stroke to 0 mm at 20 mm / min, from the load-stroke curve obtained. The hysteresis loss was calculated using the following formula. The results are shown in Tables 4 and 5. Hysteresis loss = area (oabcd) / area (oabeo) x 100 (%) The area (oabcd) represents the amount of energy lost in one cycle, and the area (oabeo) represents the total amount of energy required for tension. A small hysteresis loss means that the loss is small and the material can contract by the same amount as it is stretched, which indicates that it is easy to follow the expansion and contraction of the electrode.
[0047] <Preparation of electrodes> 5.4 parts by weight of polymer solid electrolyte precursor, 2.9 parts by weight of graphite (Nippon Graphite Industries Co., Ltd.), 11.7 parts by weight of silicon oxide ("KSC-1265" manufactured by Shin-Etsu Chemical Co., Ltd.), and 80.0 parts by weight of dimethylformamide (manufactured by Sanwa Yuka Kogyo Co., Ltd.) were added to a 200 mL disposable cup, and the disposable cup was set in a cup for a stirrer (manufactured by Thinky Corporation, Awatori Rentaro). Then, the cup was set in the main body of the stirrer, and kneaded for 1 minute at a stirring speed of 2000 rpm to obtain a slurry. The obtained slurry was applied to a Cu foil with a thickness of 50 μm, and DMF was distilled off at 60 °C for 30 minutes. After the temperature adjustment was completed, a load of 20 kg was applied using a surface press machine and pressed for 1 minute to obtain a silicon electrode. Several sheets with a diameter of 18 mm were punched out and weighed to obtain an average active material layer weight of 15 mg / cm 2 It was. Onto the surface of the obtained silicon electrode, 5.0 parts by weight of a polymer electrolyte precursor was further applied, and the temperature was controlled at 80° C. for 3 hours to obtain a silicon electrode provided with an insulating layer.
[0048] <Preparation of lithium-ion battery for evaluation> The silicon electrode with the insulating layer was punched out to a diameter of 18 mm to obtain a circular electrode. Li metal punched out to a diameter of 16 mm was then placed on the insulating layer of the electrode. This was placed in a coin cell (manufactured by Hosen Co., Ltd.) to prepare a lithium-ion battery for evaluation.
[0049] <Charge / discharge test> The initial performance of the charge / discharge test battery prepared by the following method was evaluated at 25° C. using a charge / discharge measuring device “HJ-SD8” (manufactured by Hokuto Denko Corporation). Using the constant current constant voltage charging method (also known as CCCV mode), the battery was charged up to 4.2 V at a current of 0.05 C, and then charged while maintaining 4.2 V until the current value reached 0.0025 C. After a 10-minute break, the battery was discharged down to 2.5 V at a current of 0.05 C. The charged capacity was defined as [initial charge capacity (mAh)], and the discharged capacity was defined as [initial discharge capacity (mAh)].
[0050] The above charge and discharge cycle was repeated 50 times. The battery capacity at the first charge (initial discharge capacity) and the battery capacity at the 50th charge (discharge capacity after 50 cycles) were used to calculate the discharge capacity retention rate according to the following formula. The results are shown in Tables 4 and 5. Note that the larger the value, the less the battery deteriorated. Discharge capacity retention rate (%) = [Discharge capacity at 50th cycle] / [Discharge capacity at 1st cycle] × 100
[0051] [Table 4]
[0052] [Table 5] [Industrial Applicability]
[0053] The polymer solid electrolyte of the present invention is used in fuel cells, water electrolysis devices, hydrohalic acid electrolysis devices, salt electrolysis devices, oxygen concentrators, humidity sensors, gas sensors, etc. In particular, it is suitably used as a solid electrolyte for polymer electrolyte fuel cells as vehicle-mounted power sources or home power sources.
Claims
1. A polymer solid electrolyte comprising a urethane resin and an electrolytic solution, the urethane resin is a reaction product of a composition containing a polyalkylene oxide (A-1), a polyol (A-2) having three or more hydroxyl groups, and an isocyanate (B); The crosslink density of the urethane resin is 5 to 21 mmol / kg; The electrolytic solution comprises an electrolyte and an electrolytic solution solvent (C), A polymer solid electrolyte, characterized in that the absolute value of the difference between the SP value of the polyalkylene oxide (A-1) and the SP value of the electrolyte solvent (C) is 4.0 or less.
2. 2. The polymer solid electrolyte according to claim 1, wherein the polyalkylene oxide (A-1) comprises two or more kinds of polyalkylene oxides, and the isocyanate (B) is polymeric diphenylmethane diisocyanate.
3. 3. The polymer solid electrolyte according to claim 1, wherein the electrolyte is a sulfonylimide electrolyte.
Citation Information
Patent Citations
Gel electrolyte and gel electrolyte battery
JP2007141467A
